2015
DOI: 10.1039/c4em00634h
|View full text |Cite
|
Sign up to set email alerts
|

Formation of manganese phosphate and manganese carbonate during long-term sorption of Mn2+by viable Shewanella putrefaciens: effects of contact time and temperature

Abstract: The influence of temperature (5, 10, 22 and 30 C) on the long-term (30 days) sorption of Mn 2+ by viable Shewanella putrefaciens was studied by FTIR and EXAFS. The additional Mn-removal capacity of these bacteria was found to result from the surface precipitation of Mn-containing inorganic phases. The chemical composition of the Mn-containing precipitates is temperature and contact-time dependent.Mn(II) phosphate and Mn(II) carbonate were the two major precipitates formed in 1000 mL batches at 10, Environme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 42 publications
2
3
0
Order By: Relevance
“…Specific morphologies of Mn-oxides have been described that are similar to the present observations [57]. Precipitation of Mn(II)-phosphate in cultures of Shewanella putrefaciens has been reported, as well [58]. Noteworthy, Mn-bearing phases have been characterized by EXAFS at the oxic-anoxic boundary of the eutrophic Lake Sempach (Switzerland) [59].…”
Section: Transition From Mn-to Fe-mineral Formation (50-60-m Depth)supporting
confidence: 56%
“…Specific morphologies of Mn-oxides have been described that are similar to the present observations [57]. Precipitation of Mn(II)-phosphate in cultures of Shewanella putrefaciens has been reported, as well [58]. Noteworthy, Mn-bearing phases have been characterized by EXAFS at the oxic-anoxic boundary of the eutrophic Lake Sempach (Switzerland) [59].…”
Section: Transition From Mn-to Fe-mineral Formation (50-60-m Depth)supporting
confidence: 56%
“…This finding adds to the previous reports, including the study by Chubar et al. (2015) [38] , which demonstrated that Shewanella putrefaciens can mediate the formation of both manganese phosphate and manganese carbonate. Bacteria possess diverse mechanisms to actively influence and induce mineral formation [39] .…”
Section: Resultssupporting
confidence: 84%
“…It seems likely that reactive Mn reduction was involved in H 2 S reoxidation which prevented further effluxes in the bottom water. Moreover, we can speculate that low Mn 2+ concentration in deeper sediment can be due to precipitation by sulfides or absorption by carbonates favored by the increment of pore water alkalinity induced by high sulfate reduction rates (Lovley and Phillips, 1988;Giordani et al, 1997;Chubar et al, 2015).…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 98%